The reconstruction of tail bottom Dauphin Helicopter 9M-IGB using range photogrammetry / Siti Safariah Mahat - Mahat, Siti Safariah (2018)
Visualisation in 3-dimensional of an accident wreckage is limitedly used. This paper explores how a reconstruction of a body part Dauphin Helicopter AS 365 N3/9M-IGB which is the boom tail of the helicopter by using a Photogrammetry technique, the Close Range Photogrammetry (CRP) as a counter check of the investigation done by the Air Accident Investigation Bureau (AAIB). Images of the tail boom were taken from each side of the object in order to have a high quality three dimensional view. Prior investigations, the remaining of the helicopter was laid down and arranged in two dimensional in order to investigate the cause of the accident and to identify which parts of the helicopter was missing. Therefore, the aim of this study is to define the damages of the tail that cause the crash in 3d visual. This study is conducted to develop the tail in 3-dimensional using CRP, differentiate the 3d visual with the actual image and to distinguish the impact of the detached part of the tail. The three dimensional model is generated using Agisofl Photosean software where the visualization is then compare and analyze using CAD software. In conclusion, a high accuracy of 3d image can be generated from a good orientation of a photo and with adequate light exposure.